Luminescent/magnetic PLGA-based hybrid nanocomposites: a smart nanocarrier system for targeted codelivery and dual-modality imaging in cancer theranostics - Shen X (Dove Medical Press, 2017)
Xue Shen,1 Tingting Li,1 Zhongyuan Chen,1 Yue Geng,1 Xiaoxue Xie,1 Shun Li,1,2 Hong Yang,1,2 Chunhui Wu,1,2 Yiyao Liu1,2 1Department of Biophysics, School of Life Science and Technology, 2Center for Information in Biology, University of Electronic Science and Technology of China, Chengdu, Sichuan, People’s Republic of China Abstract: Cancer diagnosis and treatment represent an urgent medical need given the rising cancer incidence over the past few decades. Cancer theranostics, namely, the combination of diagnostics and therapeutics within a single agent, are being developed using various anticancer drug-, siRNA-, or inorganic materials-loaded nanocarriers. Herein, we demonstrate a strategy of encapsulating quantum dots, superparamagnetic Fe3O4 nanocrystals, and doxorubicin (DOX) into biodegradable poly(D,L-lactic-co-glycolic acid) (PLGA) polymeric nanocomposites using the double emulsion solvent evaporation method, followed by coupling to the amine group of polyethyleneimine premodified with polyethylene glycol-folic acid (PEI-PEG-FA [PPF]) segments and adsorption of vascular endothelial growth factor (VEGF)-targeted small hairpin RNA (shRNA). VEGF is important for tumor growth, progression, and metastasis. These drug-loaded luminescent/magnetic PLGA-based hybrid nanocomposites (LDM-PLGA/PPF/VEGF shRNA) were fabricated for tumor-specific targeting, drug/gene delivery, and cancer imaging. The data showed that LDM-PLGA/PPF/VEGF shRNA nanocomposites can codeliver DOX and VEGF shRNA into tumor cells and effectively suppress VEGF expression, exhibiting remarkable synergistic antitumor effects both in vitro and in vivo. The cell viability was ~14% when treated with LDM-PLGA/PPF/VEGF shRNA nanocomposites ([DOX] =25 µg/mL), and in vivo tumor growth data showed that the tumor volume decreased by 81% compared with the saline group at 21 days postinjection. Magnetic resonance and fluorescence imaging data revealed that the luminescent/magnetic hybrid nanocomposites may also be used as an efficient nanoprobe for enhanced T2-weighted magnetic resonance and fluorescence imaging in vitro and in vivo. The present work validates the great potential of the developed multifunctional LDM-PLGA/PPF/VEGF shRNA nanocomposites as effective theranostic agents through the codelivery of drugs/genes and dual-modality imaging in cancer treatment. Keywords: doxorubicin, codelivery, dual-modality imaging, synergistic antitumor effects, VEGF shRNA